Valve condition monitoring by using acoustic emission technique - Mohd Khairul Najmie, Mohd Nor (2009)
This study was carried out to monitor valve condition monitoring by using acoustic emission technique. Two conditions were considered in this study which are good condition valve and leak valve. There are two objective of the study which is to detect acoustic emission parameter and to develop a classification method to monitor valve condition by using acoustic emission technique. The study is accomplished by analyzing the parameter hits and average rms. A hydraulic bench was used to provide water to the test rig. The first experiment is to monitor good valve condition. It is done by analyze the hits and rms collected for every rotation of the wheel handle. Then, the graph of hits plotted is compared between the graphs plotted by Hafizi (2008) to see the different characteristic of different valve. The second experiment is to monitor the leak valve. Two different valves were used in the second experiment which are gate valve and check valve. Sand and then screw was put in the valve as to make the valve leak. Then, the parameter hits and rms is measured to analyze the different between good condition valve and leak valve. The results show that there is acoustic emission activity occur when there is leak in the valve and the activity can be detected by using the acoustic emission sensor. It is also prove that the different leak will emit different acoustic emission energy.